A Review on the Behaviour of Combined Stone Columns and Pile Foundations in Soft Soils when Placed under Rigid Raft Foundation - Danish, Ahmed1; Siti Noor Linda, Taib; Tahar, Ayadat2; Alsidqi, Hasan (Akademi Sains Malaysia, 2021)
In the last few decades, it has been observed that raft foundations are very commonly used as a foundation solution for moderate to high rise structures either by resting on stone columns or on piles in soft soils. It is believed that, combining stone columns and piles in one foundation system is the more suitable foundation for medium rise structures. The combined foundation system provides a superior and more economical alternative to pile, and a more attractive alternative to stone columns in respect to ground improvement. This paper presents the review of existing studies reported in the literature in the last two decades about the behaviour of stone columns under raft foundations and piled raft foundation in soft soil, notably the failure mechanism and the bearing capacity. Also, a limited work from the literature concerning the performance of combined (pile/stone columns) foundation system in soft soil is comprised. Furthermore, very extensive ongoing research work regarding the investigation and study on the performance of combined (pile/stone columns) foundation system in soft soils is discussed. The main goals and methodology to study the performance of the combined (pile/stone columns) foundation systems in soft soil are also addressed.